2023
DOI: 10.1200/op.22.00538
|View full text |Cite
|
Sign up to set email alerts
|

Early Bereavement Psychosocial Outcomes in Parents of Children Who Died of Cancer With a Focus on Social Functioning

Abstract: PURPOSE: The early grief experience of parents of children who died of cancer remains understudied. Understanding psychosocial symptomology and functioning of parents early in their bereavement is essential to developing supportive interventions aimed at offsetting poor mental and physical outcomes. METHODS: Parents of children from two centers who died of cancer 6 to 24 months before were mailed a survey that included validated tools and additional Likert scale-based questions. We used correlation and univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Mothers’ RR for decisional regret was 10‐fold compared to fathers. This intensified maternal response is consistent with other outcomes, such as prolonged grief, impaired social functioning, post‐traumatic stress disorder, depression, anxiety, and other adverse sequelae 13,26,30,31 . However, a recent review demonstrates that fathers are less forthcoming when sharing grief experiences, 24 which may also explain observed differences in mothers’ and fathers’ risk of regret.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Mothers’ RR for decisional regret was 10‐fold compared to fathers. This intensified maternal response is consistent with other outcomes, such as prolonged grief, impaired social functioning, post‐traumatic stress disorder, depression, anxiety, and other adverse sequelae 13,26,30,31 . However, a recent review demonstrates that fathers are less forthcoming when sharing grief experiences, 24 which may also explain observed differences in mothers’ and fathers’ risk of regret.…”
Section: Discussionsupporting
confidence: 56%
“…This intensified maternal response is consistent with other outcomes, such as prolonged grief, impaired social functioning, post-traumatic stress disorder, depression, anxiety, and other adverse sequelae. 13,26,30,31 However, a recent review demonstrates that fathers are less forthcoming when sharing grief experiences, 24 which may also explain observed differences in mothers' and fathers' risk of regret. Parent-perceived child suffering is also common among bereaved parents 18,32,33 and is associated with adverse grief outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In addition, previous studies have shown that bereaved parents experience high rates of emotional and psychological pain, emphasizing the importance of providing continued bereavement services in palliative care. Snaman et al 5 found high rates of depression, anxiety, and posttraumatic stress among bereaved parents, especially among mothers who had been the primary caregivers for their children. Suttle et al 6 observed that although the pain, depression, and posttraumatic stress of bereaved parents eased over 13 months after a child's death, a high level of symptoms persisted.…”
Section: Introductionmentioning
confidence: 99%